1975
DOI: 10.1073/pnas.72.12.5061
|View full text |Cite
|
Sign up to set email alerts
|

Social structuring of mammalian populations and rate of chromosomal evolution.

Abstract: To test the hypothesis that the evolution of organisms is dependent to a large degree on gene rearrangement, we devised a way of estimating rates of evolutionary change in karyotype. This non-biochemical method is based on consideration of chromosomal variability within taxonomic groups having a fossil record. The results show that chromosomal evolution has been faster in placental mammals than in other vertebrates or molluscs. This finding is consistent with published evidence that placentals have also been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
1
6

Year Published

1982
1982
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(151 citation statements)
references
References 15 publications
6
134
1
6
Order By: Relevance
“…The mechanism might also contribute to the correlation observed between rates of speciation and rates of karyotypic change (Wilson et al 1975;Bush et al 1977;Bengtsson 1980). Speciation can be driven by adaptation to novel habitats (Schluter 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism might also contribute to the correlation observed between rates of speciation and rates of karyotypic change (Wilson et al 1975;Bush et al 1977;Bengtsson 1980). Speciation can be driven by adaptation to novel habitats (Schluter 2000).…”
Section: Discussionmentioning
confidence: 99%
“…He believes this preference is a common cause of emigration. Wilson et al (1975) believed that the apparently rapid rates of chromosomal evolution m primates and some other mammals indicate that these animals often inbreed in the wild. However, Schwartz and Armitage (1980) disagreed with this view on the basis of their data on yellow-bellied marmots, Marmotaßaviventris, which they beheve may be characteristic of many other mammalian species.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the correlations between recombination level and the biological features considered in the 2n = 16 macropodids were not significant, even though the species have a two-fold range of chiasma frequency. However, the underlying trend in the macropodids and nonmacropodids may well be the same, since the signs of the calculated correlation coefficients are the same (compare tables 5 and 6, and the 2n = 14 and 2n = 16 groups in been suggested that chromosome number varies due to other pressures such as social organisation and drift (Wilson et al, 1975;Bengtsson, 1980), which would appear to operate irrespective of their subsequent effect on the level of recombination, so that only the EC might be easily open to evolutionary modification due to its effect on recombination level (Darlington, 1932;John and Lewis 1975). The other karyotypic feature considered, DNA content, was not correlated with either of the indices of recombination.…”
Section: The Recombination Datamentioning
confidence: 99%